Eco-Friendly Management Of Early Blight Of Tomato Caused By Alternaria Solani (Journal of Plant Disease Sciences, 2022)
Aqueous plant extract from ten plant species were tested for antifungal activity against Alternaria solani, whichcauses early blight disease in tomato, in vitro and in the field. At 5, 10 and 15% concentrations, all the aqueous plant extracts inhibited mycelial growth of growth of A. solani significantly better than control. Ginger officinale inhibitedA. solani mycelial growth to the greatest extent. It was followed by Azadirchta indica and Allium sativum.Under field conditions, three sprays of aqueous plant extracts at 15-day intervals were found effective in reducing early blight disease intensity in tomato crops. spray The spray of Ginger officinale extract provided the best disease control (54.40%), followed by Azadirchta indica (47.51%) Allium sativum (41.91%) and Ocimum sanctum (41.82%).
Keywords: Alternaria solani; Early blight; Plant extracts; Tomato